Improving monitoring of water quality characteristics in artificial water storage facilities in Ukraine - Shara, Svitlana; Sharyi, Grygorii (Technology audit and production reserves, 2024)
The object of research is the hydroecological situation in the surface waters of Ukraine, indicated by the data of modern monitoring of surface waters, especially in the part of the Dnipro basin that forms the Kremenchuk Reservoir. Ukraine has not formed a holistic system of measures for monitoring and maintaining the quality of surface waters and state supervision over diseases associated with drinking water. The qualitative characteristics of drinking water are determined by the ecological state of the surface water bodies that are sources of drinking water. Therefore, this work is devoted to determining the need and ways to improve the state monitoring of the qualitative characteristics of waters in artificial water-accumulating objects and parts of the river basins that form them. The work uses scientific methods of systemic analysis, generalization and systematization, takes into account synergistic approaches in hydroecology and consideration of possible development scenarios based on the autopsy method. It is shown that diagnostic water monitoring covers only a small part of water bodies in Ukraine, and the modern hydrological monitoring network of Ukraine has up to 400 posts, including chemical pollution in half of the points, which is not enough. The state of the legal field of development of the water strategy of Ukraine, the monitoring mission of the state and the implementation of the legislative framework of Ukraine to EU requirements are analyzed, but the state of surface waters in Ukraine encourages to study the experience of water protection in European and world countries. This experience indicates that in the field of monitoring and protection of surface waters in Ukraine, a much higher and more accurate level of monitoring and a more stringent level of state regulation of water relations towards greening are needed. The work develops a structural and logical scheme of factor analysis, including systems of hydro-ecological monitoring of the formation of the aquatic environment of part of the Dnipro basin in the Kremenchuk Reservoir area. The need for systematic improvement of monitoring of water quality characteristics in artificial water storage facilities, which is the Kremenchuk Reservoir, and the need for a significant concentration of monitoring points, both in the reservoir and in the Dnipro basin that forms it, has been identified. A change in monitoring points and systematic diagnostics of reservoirs using modern capabilities of satellite sounding of water bodies within the framework of the greening of water relations in Ukraine has been proposed.